Simplify the following expression. 12a^3b^6c^5/3a^2b^4c^5

A. 4ab^2
B. 9ab^2c
C. 9ab^2
D. 4ab^2c

Answers

Answer 1
Is this how your problem is written (see attached image) If so, the answer is A. 4ab^2
Answer 2

Answer:

A.  4ab^2.

Step-by-Step Explanation.

12 a^3 b^6  c^5 / 3 a^2 b^4 c^5

Dividing each pairs of terms:

12 / 3 = 4.

a^3 / a^2 =  a.

b^6 / b^4 =  b^2.

c^5 / c^4 =  1.

So it is 4ab^2.


Related Questions

kendra has 120 stickers . 10 stickers fill a page. how many pages can she fill?​

Answers

Answer:

12 pages

Step-by-step explanation:

According to the question Kendra have 120 stickers

10 stickers fill a page

So, number of pages that can be filled be 120 stickers = [tex] \frac{120}{10} = 12[/tex]

Therefore, she can fill 12 pages by 120 stickers.

The total number of pages Kendra can fill with a total number of 120 stickers is 12 pages.

Kendra has 120 stickers, and 10 stickers fill a page.

To calculate how many pages she can fill, divide the total number of stickers by the stickers per page:

120 stickers ÷ 10 stickers/page = 12 pages.

can you guys help me out?

Answers

Answer:

5 inches

Step-by-step explanation:

V = (b² h) ÷ 3

Given that V = 25 and h = 3:

25 = (b² × 3) ÷ 3

25 = b²

b = 5

Therefore, the length of the base's sides is 5 inches.

4. If DF = 9x - 39, find EF.

Help I’m so confused!!!!

Answers

Answer:

EF =58

Step-by-step explanation:

from the illustration,

EF =DF - DE

given that DF =9x-39 , DE =47 EF=3x +10

substitute them into the formula,

3x +10=9x-39 - 47

solving for x

3x +10 =9x -86

grouping like terms

3x - 9x =-86 -10

-6x=-96

dividing through by -6

[tex] \frac{ - 6x}{ - 6} = \frac{ - 96}{ - 6} [/tex]

[tex]x = \frac{96}{6} [/tex]

[tex]x = 16[/tex]

but EF=3x+10

substitute x=16 into it to get the EF

EF= 3(16)+10

EF=48+10

EF=58

[tex]\huge\boxed{58}[/tex]

First of all, we know that [tex]DE+EF=DF[/tex], because these are two segments that make up one larger segment.

Write this as an equation.

[tex]DE+EF=DF[/tex]

[tex]47+(3x+10)=9x-39[/tex]

Remove the parentheses. [tex]47+3x+10=9x-39[/tex]

Combine the like terms. [tex]3x+57=9x-39[/tex]

Subtract [tex]9x[/tex] from both sides. [tex]-6x+57=-39[/tex]

Subtract [tex]57[/tex] from both sides. [tex]-6x=-96[/tex]

Divide both sides by [tex]-6[/tex]. [tex]x=16[/tex]

Now, find [tex]EF[/tex].

[tex]3x+10[/tex]

[tex]3(16)+10[/tex]

Multiply. [tex]48+10[/tex]

Add. [tex]\boxed{58}[/tex]

Evaluate 8a-1+0.5b8a−1+0.5b8, a, minus, 1, plus, 0, point, 5, b when a=\dfrac14a=
4
1
​ a, equals, start fraction, 1, divided by, 4, end fraction and b=10b=10b, equals, 10.

Answers

Answer: [tex]6[/tex]

Step-by-step explanation:

Given the following expression:

[tex]8a-1+0.5b[/tex]

You need to substitute the given values of "a" and "b" into the expression. Notice that these values are:

[tex]a=\frac{1}{4}\\\\b=10[/tex]

Then;

 [tex]8a-1+0.5b=8(\frac{1}{4})-1+0.5(10)[/tex]

Now you must solve the multiplications:

[tex]=\frac{8}{4}-1+5=2-1+5[/tex]

The final step is to add the numbers. Therefore, you get the following answer:

[tex]=6[/tex]

The value of the expression 8a - 1 + 0.5b evaluates to 6 for a = 1/4 and b= 10.

To evaluate the expression 8a - 1 + 0.5b when a = 1/4 and b = 10, you can substitute these values into the expression and then perform the calculations:

1. Substitute the value of a:

 

  8 * (1/4) - 1 + 0.5 * 10

2. Simplify each term:

  - First term: 8 * (1/4) = 2

  - Second term: -1

  - Third term: 0.5 * 10 = 5

3. Add the simplified terms:

  2 - 1 + 5 = 1 + 5 = 6

So, when a = 1/4 and b = 10, the expression 8a - 1 + 0.5b evaluates to 6.

Learn more about Expression here:

https://brainly.com/question/34132400

#SPJ3

PLZ HELP ME I NEED THIS ASAP

Answers

Mean = 110

Sample size = 45

Standard deviation = 6

Z score for 90% is 1.645 ( from Z-table).

Lower Limit = Mean - Z(SD/√Sample size))

Lower limit = 110 - 1.645(6/√45)

Lower limit = 108.5

Upper Limit = Mean + Z(SD/√Sample size))

Lower limit = 110 +1.645(6/√45)

Lower limit = 111.5

The interval is (108.5, 111.5)

What is the median of this list of numbers? 5, 10, 13, 7,5

Answers

Median: The middle number when all the numbers are listed in order.

To find the median of the data set shown here, we can first start by putting all the numbers in order from least to greatest.

Least to greatest - 5, 5, 7, 10, 13

Next, we locate the number that is exactly in the middle and if there is no number exactly in the middle, we find the two numbers and find halfway point between them.

The number that is exactly in the middle of the data set is 7 so our median is 7.

is 15 a perfect square​

Answers

No its not. the square root of 15 is about 3.873. Thus, the square root of 15 is not an integer, and therefore 15 is not a square number.

Answer:

No.

Step-by-step explanation:

No.

16 is a perfect square because 4 times itself is 16.

9 is a perfect square because 3 times itself is 9.

So there are no whole numbers such that when yoy square it (times it by itself) gives you 15.

Whole numbers are numbers contained within the following set:

{0,1,2,3,4,5,...}

So here are the first few perfect squares:

0 because 0(0)=0

1 because 1(1)=1.

4 because 2(2)=4.

9 because 3(3)=9.

16 because 4(4)=16.

25 because 5(5)=25.

36 because 6(6)=36.

49 because 7(7)=49.

64 because 8(8)=64.

81 because 9(9)=81.

As you can see 15 isn't in that list.

What is the value of 128^3/7

Answers

Answer:

8

Step-by-step explanation:

Catherine is 4 centimeters taller than ally, while Katrina is 5 centimeters shorter than ally. Let t represent ally's height in centimeters.

Answers

Answer:

4 is right yur

Step-by-step explanation:

Find the sq root the sq root of 5 is 2.24

Answers

Answer:  [tex]\bold{\dfrac{7-3\sqrt5}{2}}[/tex]

Step-by-step explanation:

You did great until you expanded (3 - √5)².  You forgot the middle term

[tex]\dfrac{3-\sqrt5}{3+\sqrt5}\bigg(\dfrac{3-\sqrt5}{3-\sqrt5}\bigg)\\\\\\=\dfrac{(3-\sqrt5)(3-\sqrt5)}{(3+\sqrt5)(3-\sqrt5)}\\\\\\=\dfrac{9-3\sqrt5-3\sqrt5+5}{9-3\sqrt5+3\sqrt5-5}\\\\\\=\dfrac{14-6\sqrt5}{4}\\\\\\\text{Factor out a 2 from the numerator and denominator}\\=\dfrac{2(7-3\sqrt5)}{2(2)}\\\\\\=\large\boxed{\dfrac{7-3\sqrt5}{2}}[/tex]

Find three consecutive integers whose sum is 441

Answers

Answer:

146, 147 and 148

Step-by-step explanation:

Let the three integers be x, x+1, and x+2.

(they are consecutive)

Now, we are given that their sum is 441.

So,

(x) + (x+1) + (x+2) = 441

3x + 3 = 441

3x = 438

x = 438/3

x = 146

Thus, the integers are:

x = 146

x+1 = 147

x+2 = 148

Please mark Brainliest if this helps!

1.6w - 1.2w + 3.5 + 4.7w

Answers

Answer:

8.6

Step-by-step explanation:

basically just do the order of operations

Solve for x: 5 - (x + 5) > -2(x + 4)

Answers

There you go!!! Hope I helped :)

Drag a statement or reason to each box to complete this proof.

this proof -2(x+1)=8, then x= -5

Answers

Step-by-step explanation:

distribute the -2 to (x+1) you end up with -2x-2=8 (multiplication property). Add 2 to both sides to get rid of the -2 of the left (addition property). 8+2=10. -2x=10 divide the -2 to both sides. x=-5 (division property).

Answer:

We have to prove that,

-2(x+1)=8, then x= -5

L.H.S.

[tex]-2(x+1)=8[/tex]

By distributive property,

[tex]-2x-2=8[/tex]

Adding 2 both sides ( Additive property of equality )

[tex]-2x-2+2=8+2[/tex]

[tex]-2x=10[/tex]

Divide both sides by -2 ( Division property of equality ),

[tex]\frac{-2x}{-2}=\frac{10}{-2}[/tex]

[tex]x=-5[/tex]

= R. H. S

Hence, proved....

what is 1/3 to the 2ed power

Answers

Answer:

1/9

1/3 x 1/3 = 1/9 (because 3x3 = 9)

Hey!

---------------------------------------------------------------

Solution:

Take the numerator and denominator and solve it to the 2nd power.

1² = 1

3² = 9

Put it back as a fraction.

1/9

---------------------------------------------------------------

Answer:

1/9

---------------------------------------------------------------

Hope This Helped! Good Luck!

Given: Can you use ASA postulate or the AAS Theorem to prove the triangles congruent?

Answers

I think that both apply, I may be wrong

Answer:

by ASA only

explanation:

They are reflective towards each other making them congruent

The coordinates of point A are (p, q) and coordinates of point B are (p+2q, q+2p). Provide your complete solutions and proofs in your paper homework and respond to questions or statements online. Show that the midpoint of AB is the same distance from the x-axis and y-axis

Answers

Answer:

The mid-point (p + q , q + p) of AB is the same distance from the x-axis and the y-axis

Step-by-step explanation:

* Lets explain how to solve the problem

- Any point will be equidistant from the x-axis and the y-axis must have

 equal coordinates

- Ex: point (4 , 4) is the same distance from the x-axis and the y-axis

 because the distance from the x-axis to the point is 4 (y-coordinate)

 and the distance from the y-axis and the point is 4 (x-coordinate)

- If (x , y) is the mid-point of a segment its endpoints are

 [tex](x_{1},y_{1})[/tex]  and [tex](x_{2},y_{2})[/tex], then

 [tex]x=\frac{x_{1}+x_{2}}{2}[/tex] and [tex]y=\frac{y_{1}+y_{2}}{2}[/tex]

* Lets solve the problem

∵ Point A has coordinates (p , q)

∵ Point B has coordinates (p + 2q , q + 2p)

- The mid-point of AB is (x , y)

∵ [tex]x=\frac{p+p+2q}{2}[/tex]

∴ [tex]x=\frac{2p+2q}{2}[/tex]

- Take 2 as a common factor from the terms of the numerator

∴ [tex]x=\frac{2(p+q)}{2}[/tex]

- Divide up and down by 2

∴ x = p + q

∵ [tex]y=\frac{q+q+2p}{2}[/tex]

∴ [tex]y=\frac{2q+2p}{2}[/tex]

- Take 2 as a common factor from the terms of the numerator

∴ [tex]y=\frac{2(q+p)}{2}[/tex]

- Divide up and down by 2

∴ y = q + p

The mid point of AB is (p + q , q + p)

- p + q is the same with q + p

∵ The x-coordinate of the mid point of AB is p + q

∵ The y-coordinate of the mid point of AB is q + p

∵ p + q = q + p

∴ The coordinates of the mid-point of AB are equal

- According the explanation above

The mid-point (p + q , q + p) of AB is the same distance from the

   x-axis and the y-axis

If a+b+c=7 and ab+bc+ca=20 find the value of a^2+b^2+c^2

Answers

Answer:

9

Step-by-step explanation:

Using the identity

(a + b + c)² = a² + b² + c² + 2(ab + bc + ca)

Subtract 2(ab + bc + ca) from both sides, then

a² + b² + c² = (a + b + c)² - 2(ab + bc + ca) = 7² - 2(20) = 49 - 40 = 9

The price of a house increased from $400,000 to $500,000 in one year. What is the percent increase?

Answers

Answer:

80%

Step-by-step explanation:

Final answer:

The percent increase in the price of the house is 25%. This is calculated using the formula for percent increase: (Final value - Initial value) / Initial value * 100.

Explanation:

The question is asking for the percent increase in the price of a house. The formula for calculating percent increase is: (Final value - Initial value) / Initial value * 100. In this case, the initial value is the original house price of $400,000 and the final value is the new house price of $500,000.

So, the calculation will be: ($500,000 - $400,000) / $400,000 * 100 = 25%.

Therefore, the price of the house increased by 25% over the year.

Learn more about percent increase here:

https://brainly.com/question/5449967

#SPJ2

what is the value of s(6)

Answers

Answer:

6s

Step-by-step explanation:

sx6 = 6s

Prove the inequality.

c+ 1/c ≥2 for c>0

Answers

Final answer:

The inequality c + 1/c ≥ 2 for c > 0 is proven by using the AM-GM inequality method. By applying this method, we find that the arithmetic mean of the variables is indeed greater or equal to 2, hence confirming the inequality.

Explanation:

To solve the inequality c + 1/c ≥ 2 for c > 0, we can use the AM-GM (Arithmetic Mean - Geometric Mean) inequality method.

According to AM-GM inequality, for any positive numbers a, b, the arithmetic mean is always greater or equal to the geometric mean. In notation: (a + b)/2 ≥ sqrt(a * b). Applying this to our problem where a = c and b = 1/c, we get (c + 1/c) / 2 ≥ sqrt(c * 1/c). This simplifies to c + 1/c ≥ 2*1 = 2, therefore our inequality is confirmed.

Learn more about Inequality here:

https://brainly.com/question/40505701

#SPJ12

The inequality c + 1/c ≥ 2 for c > 0 is proven using the AM-GM inequality by setting a = c and b = 1/c, showing that their arithmetic mean is always greater or equal to their geometric mean.

To prove the inequality c + 1/c ≥ 2 for c > 0, we can apply the AM-GM inequality which stands for Arithmetic Mean - Geometric Mean inequality. The AM-GM inequality states that for any non-negative real numbers a and b, the arithmetic mean is always greater than or equal to the geometric mean. That is, (a + b)/2 ≥ √(ab).

In our case, we can let a = c and b = 1/c. Then, according to the AM-GM inequality, we get:

(c + 1/c)/2 ≥ √(c * 1/c)(c + 1/c)/2 ≥ √(1)(c + 1/c)/2 ≥ 1

When we multiply both sides of the inequality by 2, we get:

c + 1/c ≥ 2

This completes the proof for the inequality c + 1/c ≥ 2 when c > 0.

What is the gcf of 42 and 10

Answers

Answer:

2

Step-by-step explanation:

Make a list

10: 1, 2, 5, 10

42: 1, 2, 3, 6, 7, 14, 21

Round 42395 to the nearest ten thousand

Answers

Answer:

40000

Step-by-step explanation:

4(2)395

if it smaller than 5 round down

if its lager than 5 round up

How do I identify the rate of change on a linear function?

Answers

Answer:

Slope is the ratio of the vertical and horizontal changes between two points on a surface or a line. The vertical change between two points is called the rise, and the horizontal change is called the run. The slope equals the rise divided by the run.

The average rate of change is constant for a linear function.
Another way to state this is that the average rate of change remains the same for the entire domain of a linear function.
If the linear function is
y
=
7
x
+
12
then the average rate of change is 7 over any interval selected.
Slope intercept form
y
=
m
x
+
b
, where
m
is the slope.

Solve v= 1/3 bh for h

Answers

Answer:

Step-by-step explanation:

v= 1/3 bh

multiply by : 3

3v = bh

dividid by b : h = 3v/b

Final answer:

To solve for h in the equation v = (1/3)bh, you need to isolate h on one side. Multiply both sides by 3 to eliminate the fraction, then divide both sides by b to solve for h.

Explanation:

To solve the equation v = (1/3)bh for h, we need to isolate h on one side of the equation.

First, we can multiply both sides of the equation by 3 to get rid of the fraction: 3v = bh.

Next, to solve for h, we divide both sides of the equation by b. This gives us the final answer: h = 3v / b.

Learn more about Solving equations here:

https://brainly.com/question/18322830

#SPJ2

Can someone help me with this question it is so confusing

Answers

we know it takes 20lbs of Olive to make 3 liters of oil, we also know that the orchard for a whole year gets 3000 lbs, how much oil is there in those 3000 lbs for the year?

[tex]\bf \begin{array}{ccll} \stackrel{olive}{lbs}&\stackrel{olive~oil}{liters}\\ \cline{1-2} 20&3\\ 3000&x \end{array}\implies \cfrac{20}{3000}=\cfrac{3}{x}\implies \cfrac{1}{150}=\cfrac{3}{x}\implies x= 450[/tex]

f(x) = 8x – 2
g(x) = 9x + 2
What is h(x) = f(x) – g(x)?

Options:
h(x) = 17x + 14
h(x) = x + 4
h(x) = –x – 4
h(x) = –x + 14

Answers

Answer:

-x-4

Step-by-step explanation:

8x-2-(9x+2)

8x-2-9x-2

-x-4

Function h(x) = f(x) – g(x) = -x - 4

What is a function?

Function, in mathematics, an expression, rule, or law that defines a relationship between one variable (the independent variable) and another variable (the dependent variable).

Given functions

f(x) = 8x – 2

g(x) = 9x + 2

h(x) = f(x) – g(x)

h(x) = (8x – 2) - (9x + 2)

h(x) = 8x - 2 -9x - 2

h(x) = (8x - 9x) + (-2 - 2)

h(x) = -x - 4

Hence, h(x) = -x - 4

Find out more information about function here

https://brainly.com/question/12544664

#SPJ3

Please select the word from the list that best fits the definition
Understands how formulas are used
Interpersonal
Musical
Body-Kinesthetic
Spatial
Linguistic
Intrapersonal
Logical-Mathematical

Answers

Answer:

Logical-Mathematical

Step-by-step explanation:

According to the theory of multiple intelligences, human intelligence has 8 different modalities (musical-rhythmic, visual-spatial, verbal-linguistic, logical-mathematical, bodily-kinesthetic, interpersonal, intrapersonal, naturalistic). In order to understand how formulas are used, logical-mathematical intelligence is used.

Final answer:

The term that corresponds to understanding how formulas are used is Logical-Mathematical. This refers to an individual's proficiency in carrying out mathematical operations and understanding complex mathematical problems, including the use of formulas.

Explanation:

The word from the list that best fits the definition 'Understands how formulas are used' is Logical-Mathematical. This term is one of Howard Gardner's Multiple Intelligences and it refers to the ability to calculate, quantify, consider propositions and hypotheses, and carry out complete mathematical operations. In an educational setting, people who are strong in logical-mathematical intelligence can understand complex problems, detect patterns, and excel in mathematics, with skills such as understanding formulas playing a key role.

Learn more about Logical-Mathematical Intelligence here:

https://brainly.com/question/36415511

#SPJ6

lim (x^3-8)/(x)
x-2 ​

Answers

Here you go!!! Hope this helps

Teresa’s age is 5 years more than twice Ben’s age. If Ben is x years old, the expression _____ gives the sum of Ben’s and Teresa’s ages. If Ben is 7 years old, the sum of Ben’s and Teresa’s ages is _____ years.

Answers

Using a system of equations, it is found that:

If Ben is x years old, the expression 3x + 5 gives the sum of Ben’s and Teresa’s ages. If Ben is 7 years old, the sum of Ben’s and Teresa’s ages is 26 years.

What is a system of equations?

A system of equations is when two or more variables are related, and equations are built to find the values of each variable.

In this problem, the variables are given by:

Variable x: Ben's age.Variable y: Teresa's age.

Teresa’s age is 5 years more than twice Ben’s age, hence:

y = 2x + 5

The sum of their ages is:

x + y = x + 2x + 5 = 3x + 5.

Ben is 7 years old, hence the sum is given by:

3(7) + 5 = 26.

Then:

If Ben is x years old, the expression 3x + 5 gives the sum of Ben’s and Teresa’s ages. If Ben is 7 years old, the sum of Ben’s and Teresa’s ages is 26 years.

More can be learned about a system of equations at https://brainly.com/question/24342899

Final answer:

The sum of Ben's and Teresa's ages is represented by the expression 3x + 5, and when Ben is 7 years old, their total age is 26 years.

Explanation:

The expression to represent the sum of Ben's age and Teresa's age, given that Ben is x years old and Teresa's age is 5 years more than twice Ben's age, is 2x + 5 + x. This can also be simplified to 3x + 5.

When Ben is 7 years old, we plug in the value 7 for x in the simplified expression to calculate the sum of their ages: 3(7) + 5, which equals 21 + 5.

Therefore, the sum of Ben's and Teresa's ages when Ben is 7 years old is 26 years.

Other Questions
Which of the following diseases is more likely to occur through contact with contaminated water in industrialized countries than in non-industrialized countries?a. hepatitis Ab. typhoid fever c. legionellosis d. hepatitis B e. tuberculosis A scientist measures 1062 mL of a substance with a density of 0.023 g/mL. What is themass of the substance? True or false the two parts of the Stone Age are the old Stone Age sure the old Stone Age and the pre historic Stone Age The car starts from rest and accelerates with an acceleration of 2 m/s^2 for 5 s. It then travels at a constant speed for 20 s, before decelerating at -5 m/s^2 until it reaches zero speed. How much distance did the car cover during this journey. Mejor comoMas Buena comoMejor queMas buena que Write an equation of the line with the given slope, m, and y-intercept (0.b).m=8, b = 3The equation is______(Simplify your answer. Type your answer in slope-intercept form. Use integers or fractions for any numbers in the equation.) Multi step equation and check 12x+3-1=35 Please help ASAP, Im desperate!! Choose one of the artists featured in this section, and then find another artwork by that artist. (If you do not want to use one of these artists, choose another artist whose artwork you like.) You can find the artwork online, in a book, or even at a museum. The artists featured in this section: -Paul GustaveDor -Katsushika Hokusai Leonardo da Vinci -Franz Marc -Richard F. Outcault 1. What is the artist's name? What is the name of the artwork? 2. What is the subject of the artwork? (Explain in two to three sentences.) 3. What tools did the artist use to make the artwork? (For example, paint, ink, a computer, etc.) 4. How did the artist use lines in the artwork? What was the effect of that usage on the artwork? (Explain in four to five sentences.) 5. Why did you choose this artwork as an example of the use of lines? (Explain in four to five sentences.) What year was King Philip the I born What is the fastest way to administer nicotine to the brain?a. Intravenous route (IV)b. Snortingc. Chewingd. Smokinge. IV and smoking are equally fast Write an equation that can be used to find the area of any 10 square floor tiles If two planes are perpendicular to the same line, then.A. they form a straight lineB. they are perpendicular to each otherC. they are parallelD. not enough information The atmospheric pressure reads "35.2". What is the "gage pressure"? 7. For the system PCls(g) PC13(g) + Cl2(g) Kis 26 at 300C. In a 5.0-L flask, a gaseous mixture consists of all three gases with partial pressure as follows: Ppcis = 0.012 atm, Pc2=0.45 atm, Ppci3 -0.90 atm. a) Is the mixture at equilibrium? Explain. b) If it is not at equilibrium, which way will the system shift to establish equilibrium? What does the story of beer tell you about social and gender in ancient southwest Asia and Egypt? Calculate the freezing point of a solution made from 220g of octane (C Hua), molar mass = 114,0 gmol dissolved in 1480 g of benzene. Benzene freezes at 5.50"C and its Kvalue is 5.12C/m. -1.16C 0.98C 666"C 12 2C 5.49C 10 12 AM A A 2019 Backspace yuo Pill L Answer these questions: (3 to 8 paragraphs for each question)Assignment Instructions: Prepare a 4-10-page essay answering the questions below6. What is dark energy? How much of the universe is thought to be dark energy? Propose a hypothesis for the evolution of life on earth from single-celled organisms to multicellular organisms. What is the most significant step in the evolution of multicellularity? The school board asked Han to conduct a study on the attitudes of faculty regarding the proposed school uniform policy. Han stops by the teachers' lounge and surveys the faculty present. Which nonrandom sampling approach did Han employ? which britsh document established the right of free speech that was reinforced by this excerpt